2021
DOI: 10.1016/j.nicl.2021.102648
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high field (7T) functional magnetic resonance imaging in amyotrophic lateral sclerosis: a pilot study

Abstract: Highlights Participants with ALS exhibited impaired function between the cortex and cerebellum. The cerebellum is associated with complex motor and cognitive processing tasks. These findings add to the growing number of ALS reports implicating the cerebellum.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Radiologically, the BCNSB appears intact in ALS patients on standard imaging techniques, in contrast to multiple sclerosis and other CNS inflammatory conditions whereby BCNSB disruption is typically demonstrated by gadolinium extravasation on MRI. While early clinical ALS studies using novel 7T MRI scanners have largely explored the CNS anatomy and connectivity (Verstraete et al, 2010b ; Cosottini et al, 2016 ; Barry et al, 2021 ), BCNSB leakage has not been extensively investigated with this technique. Of note, indirect measures of BBB integrity such as microbleeds in ALS were not increased as measured by 7T MRI (Verstraete et al, 2010a ).…”
Section: Resultsmentioning
confidence: 99%
“…Radiologically, the BCNSB appears intact in ALS patients on standard imaging techniques, in contrast to multiple sclerosis and other CNS inflammatory conditions whereby BCNSB disruption is typically demonstrated by gadolinium extravasation on MRI. While early clinical ALS studies using novel 7T MRI scanners have largely explored the CNS anatomy and connectivity (Verstraete et al, 2010b ; Cosottini et al, 2016 ; Barry et al, 2021 ), BCNSB leakage has not been extensively investigated with this technique. Of note, indirect measures of BBB integrity such as microbleeds in ALS were not increased as measured by 7T MRI (Verstraete et al, 2010a ).…”
Section: Resultsmentioning
confidence: 99%
“…3 TRs = 10.5 s; ~0.1 Hz), it is sufficient to track the change of resting-state signals, the peaks of which are usually detected within a frequency of 0.03-0.04 Hz (Zuo et al, 2010, Xue et al, 2014, Yuen et al, 2019, Bajaj et al, 2014) in the gray matter. Furthermore, it has been reported that conventional resting-state analyses are not significantly altered by TR (Huotari et al, 2019), and methods employing relatively slow sampling have succeeded in tracking laminar dynamics (e.g., 3960ms (Sharoh et al, 2019), 5000ms (Barry et al, 2021), 8300ms (Huber et al, 2020)). Despite the advantages of TR-external EPIK over conventional EPI, the GE nature of the technique makes it susceptible to vein-derived contamination, just as any other GE-EPI sequence.…”
Section: Discussionmentioning
confidence: 99%
“…However, since rs‐fMRI focuses on low‐frequency fluctuations (<0.1 Hz), conventional data analyses require a TR of 5 s to cope with the Nyquist sampling of the upper limit (Berman et al, 2021 ). Accordingly, the use of a long TR for rs‐fMRI has also been demonstrated in previous publications: TR of 3960, 5000 and 5856 ms (Barry et al, 2021 ; Berman et al, 2021 ; Sharoh et al, 2019 ). Depending on the method selected from the literature, it may be possible to achieve an increased spatial resolution or larger slice coverage by a protocol adjustment.…”
Section: Discussionmentioning
confidence: 53%
“…Accordingly, the use of a long TR for rs-fMRI has also been demonstrated in previous publications: TR of 3960, 5000 and 5856 ms (Barry et al, 2021;Berman et al, 2021;Sharoh et al, 2019). Depending on the method selected from the literature, it may be possible to achieve an increased spatial resolution or larger slice coverage by a protocol adjustment.…”
Section: Rsn Results For An Isovoxel Protocolmentioning
confidence: 81%